Economic Performance, Individual Evaluations, and the Vote: Investigating the Causal Mechanism - Becher, Michael (https://www.journals.uchicago.edu/doi/10.1017/S0022381613000959, 2013)
While there are many studies on the impact of the economy on elections, there is little evidence on the full mechanism of economic voting implied by performance-based theories of elections. Addressing the scarcity of evidence on the mechanism, this study provides the first estimates of the linkage between macroeconomic performance, individual economic evaluations, and vote choice. Building on recent advances in the statistical analysis of causal mechanisms, we conduct a causal mediation analysis in a data set covering 151 surveys in 18 countries. We find that the effect of economic performance on the incumbent vote is largely accounted for by voters’ retrospective evaluations of the national economy. The effect is stronger in contexts where policymaking power is concentrated rather than dispersed. Altogether, the results imply that the performance-based channel of voting is more relevant in accounting for election outcomes than suggested by recent individual-level studies.